Beyond Vocation or Avocation: Regenerative Food Growing as a Way of Life - Ruitenberg, Claudia (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2022)
The binary work/leisure continues to be used to categorize many human activities, but falls short for ways of life in which a particular set of values undergirds all activities. This paper discusses regenerative forms of growing and harvesting food – in particular, permaculture and natural farming – as values-based practices that blur the boundaries between work and leisure. While there are other values-based practices that unite vocation and avocation, permaculture and natural farming are of special interest because they respond to young climate activists’ desire for ways of life that acknowledge that human activities are part of ecosystems, and that accept the need for an ecological transition.